Meningkatkan Minat dan Prestasi Belajar Materi Usaha dan Gaya Melalui Metode Media Visual pada Siswa Kelas VIII-I SMP Negeri 2 Pare Kabupaten Kediri - Na, Husnaini (Jurnal Simki Postgraduate, 2023)
This study aims to describe science with the application of the Visual Media method which can improve student achievement in the material Effort and Style. This study used a Class Action Design (PTK) which consisted of two cycles. Research data collection was carried out from September to November 2022. The results of the research in the form of student learning activities and achievements were obtained through tests at the end of each cycle. The results showed that students' interest increased by (14.58%) in cycle 1, from 68.42% to 83% in cycle 2. In increasing learning achievement, the number of students who met the KKM standard in cycle 1 was 22 students (59 %), and students who met the KKM standard in cycle 2 were 34 students (95%). The percentage increase was 36% from cycle 1. So it can be concluded that the application of the Visual Media method can improve student achievement in class VIII-I SMP Negeri 2 Pare on the subject of Business and Style.